Biology of melanocytes in mammals - Cui, Ying-Zhe; Man, Xiao-Yong (Frontiers in Cell and Developmental Biology, 2023)
Melanocytes, which originate from the neuroectoderm, are specialized cells responsible for producing pigments and possessing a dendritic morphology. These cells migrate to the epidermis and follicles, contributing to skin and hair pigmentation during embryonic development. The remarkable self-renewal capacity of melanocytes enables them to effectively restore hair and skin pigmentation. The synthesis of melanin to safeguard the skin against damage caused by ultraviolet radiation, as well as the enigmatic immune function of melanocytes, demonstrate their indispensable contributions to maintaining cutaneous homeostasis. The regulation of cutaneous pigmentation involves an intricate network influenced by intrinsic cellular signals within melanocytes and extracellular cues. Therefore, this paper provides a comprehensive review of the role of melanocytes in skin biology. This in-depth analysis could open novel avenues for research aimed at the prevention and treatment of skin disorders.